Sumber-sumber Pendapatan dan Pengeluaran Negara Islam - Rahman, Muh Fudhail (Faculty of Shariah and Law, 2013)
The State is a place for some people to realize a better life. One of the most urgent instruments is the existence of government as manager of the State. Through the national budget of a state, it taps revenues and expenditures will be managed in a planned manner with the aim at prosperity of all people. For example, increasing the rate of economic growth (pro-growth), expanding new jobs (pro-job), and improve protection programs for the poor (pro-poor). In the classical discourse, Islamic government that had been present in the scene of history, has also pointed out the state opinion forms. This article briefly describes the ratio of budget revenues and expenditures between Islam and the Indonesian government systemDOI: 10.15408/aiq.v5i2.2120